PERAN ORANG TUA DALAM PEMBELAJARAN DARING MASA PANDEMI COVID-19 DI KELAS II SD ISLAM CAHAYA ILMU SEMARANG - Umi Makhmudah, Nurul; Listyarini, Ikha; Yusuf Setia Wardana, Muhamad (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
This research was motivated by a pandemic condition that resulted in children having to go to school from home. This problem is increasingly difficult for parents or children to achieve real educational goals. The problem in this study is how the role of parents in online learning during the covid-19 pandemic in second-grade students of Islamic Elementary School Cahaya Ilmu Semarang. As well as the difficulties experienced by parents in accompanying their children to study during the pandemic. The purpose of this study was to determine the role and difficulties of parents in assisting children in learning during the COVID-19 pandemic. The type of research used in this research is qualitative research. The subject of this research is parents. The data of this study were obtained through interviews, observation, and documentation. Parents have a very important role in assisting children to learn during the pandemic. In addition, parents have difficulty in assisting their children to learn. Children's moods are easy to change and there is limited time to accompany children to learn.